Multiple and complex eye injuries in children - G.Sh. Arzhimatova; O.V. Karaseva; E.A. Koroleva; G.M. Chernakova (РМЖ "Клиническая офтальмология")
G.Sh. Arzhimatova1,2, O.V. Karaseva3, E.A. Koroleva3, G.M. Chernakova2 1Russian Medical Academy of Continuous Professional Education, Moscow,   Russian Federation 2S.P. Botkin City Clinical Hospital, Moscow, Russian Federation 3Research Institute for Children's Emergency Surgery and Trauma, Moscow, Russian Federation Aim: to identify the medical and epidemiological hallmarks of eye damage in children with complex and multiple injuries in a specialized surgical department. Patients and Methods: this study included 403 children aged 1 month to 18 years with eye injuries associated with multiple or complex injuries of varying severity on the day before hospital admission. All children were admitted between 2014 and 2020. The following data were evaluated: patient's age, gender, severity of complex trauma based on the ISS score, cause of trauma, combination of anatomical areas involved. Results: among children with mechanical complex eye injuries, 255 (63%) were boys and 148 (37%) were girls. The mean age of boys was 10.2±0.34 years, and the mean age of girls was 8.5±0.42 years. Furthermore, more than half (67.5%) of those included in the study were school-aged children and adolescents. The most common types of injuries were those resulting from falls from height, school, sports, gunshot/mine blast, and street incidents. In more than half of the children (n=227, 56.4%), orbital traumas affecting the walls and/or content were reported. The most common type of eye damage was a complex damage to the orbit and ocular adnexa (most often as a periorbital hematoma). The percentage of children with multiple fractures of the orbital walls increases with an increase in the severity of polytrauma. Conclusions: children most often received mechanical complex eye injuries as a result of road traffic accidents. The percentage of children with minor, moderate, and severe complex injuries (assessed by the ISS) was 47.1%, 18.4%, and 33.5%, respectively. Orbital fractures are the most common surgical entities in children with complex mechanical eye injuries. Unilateral orbital fractures were diagnosed in 56.4% of cases, while bilateral orbital fractures were diagnosed in 17.9%. In the majority of instances, mechanical complex eye injuries are associated with traumatic brain injury (99%). Keywords: complex eye injuries, multiple injury, combined injury, mechanical complex eye injury, orbital fracture, orbital injury, morbidity pattern, damage to eye. For citation: Arzhimatova G.Sh., Karaseva O.V., Koroleva E.A., Chernakova G.M. Multiple and complex eye injuries in children. Russian Journal of Clinical Ophthalmology. 2024;24(2):78–82 (in Russ.). DOI: 10.32364/2311-7729-2024-24-2-6.